A metabolomics study of the intervention effect of Tartary buckwheat on hyperlipidemia mice. Issue 10 (7th August 2022) - Zhou, Xiaoli; Li, Senjie; Zhou, Yiming; Zhang, Huan; Yan, Beibei; Wang, Hong; Xiao, Ying
Abstract: Tartary buckwheat can improve hyperlipidemia and affect the changes of metabolic pathways to the body. In this study, we use LC/MS to obtain metabolic fingerprints of plasma samples collected from control (LFD), high‐fat diet (HFD), Tartary buckwheat protein (BWP), and Tartary buckwheat starch (BWS). Using the metabolic network database, through OPLS‐DA, the potential biomarkers and pathways of BWP and BWS intervention in hyperlipidemia mice are initially determined. The results showed that there are 30 metabolites in total, among which linoleic acid, glycerol, phosphatidyl, ethanolamine, and galactose ceramide are the most important differentially expressed metabolites in BWP and BWS plasma samples. These metabolites are involved in eight metabolic pathways, such as linoleic acid metabolism, arachidonic acid metabolism. Tartary buckwheat can alleviate the symptoms of hyperlipidemia in mice by affecting the above‐mentioned metabolic pathways. This research has a profound impact on the development of nutritious foods of buckwheat. Practical applications: Tartary buckwheat, also known as wild buckwheat, is a typical embodiment homology of medicine and food. We have clarified that the protein and starch extracted from tartary buckwheat have the function of reducing blood lipids. It is expected to be applied to functional food materials in the health food market. Also, the effects of tartary buckwheat protein and starch in improving metabolic pathways can be generally applied as a physiological active compound of functional food supplements. Abstract : Tartary buckwheat can reduce blood lipids in mice induced by high‐fat diet. Analysis and identification of the metabolites of buckwheat showed that there were 30 in total. The lipid‐lowering mechanism of tartary buckwheat involves eight metabolic pathways.